Beyond the facts : the production and evaluation of the pilot episode of a current affairs television series for local teenagers. - Latha Kannan. (2008)
The purpose of this thesis was to produce conceptualise and produce a pilot episode of a current affairs series targetted at teenagers between the ages of 13-16. The background interest that led to this study was my personal experience with teenagers in this age group. I found that although they were interested in global events, they were unable to comprehend it fully because of their lack of background information. This thesis therefore set out to provide them that background information via the means of a half-hour television series. The research that went into this study was primarily two-fold - literature reviews and an analysis of all past informational programmes that had been produced for teenagers locally.